Kunstaankopen Enschede 1996-97. - Kroon, Carlo; Roncken, Stan; Ticheler, Ruud; Tuerlings, Maria; Weysters, Arend-Jan (Enschede : gemeente Enschede, 1997)
Bensca, Caro ; D, Eddie ; Ebeling Koning, Hans ; Ebeling Koning, Koen ; Gunn, Reggy ; Lamers, Ine ; Nijeboer, Evelien ; Ophuis, Ronald ; Santos, Manuel dos ; Smits, Kees ; Schepens, Theo ; de Ven, Lidwien van
Nederlands
boek
Keywords: Enschede